QT interval analysis in type 2 diabetic patients - Msayer, Kawthar H. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: The electrocardiographic QT interval has been extensively studied in diabetes mellitus. Recently, there has been increasing interest in the relationship between diabetes and QT abnormalities .The QT interval, which is easily obtained from a standard resting electrocardiogram( ECG), reflected the total duration of ventricular myocardial depolarization and repolarization. The heart rate corrected QT interval (QTc) by Bazett's formula on the electrocardiogram has been proposed as a risk factor for ventricular arrhythmias in diabetes mellitus. Dispersion of QT(QTd) is defined as the difference between maximum and minimum QT interval QT interval on 12 lead ECG, which reflected spatial ventricular repolarization in homogeneity ,has been report to increase in diabetic subjects compare with non diabetic subjects.Patients and Methods: Type 2 diabetic patients (n=80) and healthy subjects (n=25) were required to have 12-lead ECG suitable for QT analysis ,QT interval was measured in each lead tofound(maximum, minimum, and mean ).QT interval vary according to the heart rate, it can be corrected using Bazett's formula to give QTc interval, and to found (maximum, minimum, and mean).Dispersion of QT interval(QTd) was calculate using the difference between the maximum and minimum QT interval duration as same as for dispersion of corrected QT interval(QTcd).Result: There were significant difference in QT interval indices between type 2 diabetic and healthy subjects (P